Inflammation in Cerebral Venous Thrombosis - Ding, Jiayue; Song, Baoying; Xie, Xiran; Li, Xaingyu; Chen, Zhiying; Wang, Zhongao; Pan, Liqun; Lan, Duo; Meng, Ran (Frontiers in Immunology, 2022)
Cerebral venous thrombosis (CVT) is a rare form of cerebrovascular disease that impairs people’s well-being and quality of life. Inflammation is considered to play an important role in CVT initiation and progression. Several studies have reported the important role of leukocytes, proinflammatory cytokines, and adherence molecules in the CVT-related inflammatory process. Moreover, inflammatory factors exacerbate CVT-induced brain tissue injury leading to poor prognosis. Based on clinical observations, emerging evidence shows that peripheral blood inflammatory biomarkers—especially neutrophil to lymphocyte ratio (NLR) and lymphocyte count—are correlated with CVT [MD(95%CI), 0.74(0.11, 1.38), p=0.02 and -0.29(-0.51, -0.06), p=0.01, respectively]. Moreover, increased NLR and systemic immune-inflammation index (SII) portend poor patient outcomes. Evidence accumulated since the outbreak of coronavirus disease-19 (COVID-19) indicates that COVID-19 infection and COVID-19 vaccine can induce CVT through inflammatory reactions. Given the poor understanding of the association between inflammation and CVT, many conundrums remain unsolved. Further investigations are needed to elucidate the exact relationship between inflammation and CVT in the future.